Diagnosis of consumption of turtles (Testudines) in the municipality of Abaetetuba, Pará: Implications for the conservation of species (Research, Society and Development, 2022)
The objective of this work was to carry out a survey about the conceptions of the residents of the municipality of Abaetetuba in the state of Pará, about the use and consumption of turtles in the region. The study area covered 38 neighborhoods and 72 islands, which constitute the so-called islands region of the Municipality of Abaetetuba in the state of Pará, northern region of Brazil. For data acquisition, online forms were applied in October 2020 and later the data were processed through the Microsoft Office Excel program (Version 2016). 146 responses were obtained covering 14 neighborhoods and 9 communities, including islands and branches. About 68% (N=100) were female and 32% (N=46) were male. Of those interviewed, 90% (N=129) live in urban areas and 10% (N=17) in rural areas. Regarding consumption, 14% (N=20) had already consumed turtles while 86% (N=126) said they had never consumed them. Among consumers of this type of meat (N=20), 100% stated that they know other people who have already consumed it, as well as of the non-consumers (N=126), 56% (N=71) know people who have already eaten this type of meat. of meat. Regarding meat consumption, the most cited species was the tortoise (51.71%), followed by Perema (14.19%) and Tracajá (4.6%). This study presents preliminary data for the development of management and conservation plans for chelonian populations in the Abaetetuba region.